Segregation and the Legality of Religious Diversity: Case Studies of Religiously Labeled Schools - Ali Halidin; Sitti Zakiah; Ishak; Muh. Hasbi (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2022)
For the people of Indonesia, religious plurality and a pluralistic society have become the most pressing concerns. The language and thought of religion and multiculturalism are constantly complex, as is the management of diversity, because religious diversity can create either conflict or discord, depending on how we view the meaning of religious pluralism and diversity. If the multiplicity of religions is regarded as a threat and it is conceivable for tension and conflict between religions to arise, then pluralism will be the most crucial factor for the Indonesian people to invest in. In contrast, the reality of social inferiority would contribute to the spread of tolerance and concord, as well as the orthodoxy practiced by the populace. The relationship between religions in Indonesia today exhibits a positive effect on harmony. It is vital to bolster the concept of pluralism in the education of religious principles. From the standpoint of religion, the author examines the concept of pluralistic education. This is qualitative research. Observation, in-depth interviews, document studies, source evaluation, and information validation were employed as data-gathering instruments. While the obtained data were analyzed using a descriptive approach, which consisted of observing the phenomena that occur, displaying and reducing data, and then mapping the problem and drawing broad conclusions, the data were obtained by observing the phenomena that occur, displaying and reducing data, and then mapping the problem and drawing broad conclusions. As demonstrated by this study's findings for schools with religious names, Islamic, Catholic, Christian, Hindu, and Buddhist institutions, among others, were founded with the intention of serving as a platform for the construction and advancement of culture. Human education includes So aggregation arises as a characteristic of religious schools as patrons to protect the nation's morality in accordance with the methods of these many schools and become the representatives of religion diversity. Religion also forms a branding on schools to give the appearance that a nation's morals are refined and submissive to its religious standards. In addition, it was discovered that religious schools in South Sulawesi are highly costly, with elite school settings, and that the average student hails from upper-middle-class families, particularly in large cities like Makassar. such as the Cendrawasih Catholic Schools, Brothers, Hindu Darma, and the Athirah Islamic School and Al-Azhar, but there are also other inexpensive Islamic schools, like Muhammadiyah and NU Schools.